Thermomechanical Noise Characterization in Fully Monolithic CMOS-MEMS Resonators - Rafel Perelló-Roig; Jaume Verd; Sebastià Bota; Jaume Segura (Sensors, 2018)
We analyzed experimentally the noise characteristics of fully integrated CMOS-MEMS resonators to determine the overall thermomechanical noise and its impact on the limit of detection at the system level. Measurements from four MEMS resonator geometries designed for ultrasensitive detection operating between 2-MHz and 8-MHz monolithically integrated with a low-noise CMOS capacitive readout circuit were analyzed and used to determine the resolution achieved in terms of displacement and capacitance variation. The CMOS-MEMS system provides unprecedented detection resolution of 11 yF·Hz−1/2 equivalent to a minimum detectable displacement (MDD) of 13 fm·Hz−1/2, enabling noise characterization that is experimentally demonstrated by thermomechanical noise detection and compared to theoretical model values.